Raman light scattering in pseudospin-electron model at strong pseudospin-electron interaction - Mysakovych, T.S.; Stasyuk, I.V. (Condensed Matter Physics, 2004)
Anharmonic phonon contributions to Raman scattering in locally anharmonic crystal systems in the framework of the pseudospin-electron model with tunneling splitting of levels are investigated. The case of strong pseudospin-electron coupling is considered. Pseudospin and electron contributions to scattering are taken into account. Frequency dependences of Raman scattering intensity for different values of model parameters and for different polarization of scattering and incident light are investigated.